The relationship between teacher care and Chinese college students’ physical education class learning satisfaction: the chain mediation effect of exercise enjoyment and exercise self-efficacy - Chen, Haixiong; Xiang, Jun (Frontiers in Psychology, 2025)
BackgroundTeacher care is a key factor influencing college students’ satisfaction with physical education (PE) courses. Insufficient teacher care may diminish students’ learning motivation and exercise engagement, affecting their physical and mental well-being. Yet, the mechanisms linking teacher care to PE learning satisfaction remain unclear, particularly the roles of exercise enjoyment and exercise self-efficacy.ObjectiveTo investigate the impact of teacher care on college students’ physical education class learning satisfaction in Chinese universities and to validate the mediating role of exercise enjoyment and exercise self-efficacy between the two.MethodsA clustered convenience sample of 1,198 college students from Chinese universities completed the Teacher Care Scale, Physical Education Class Satisfaction Scale, Exercise Enjoyment Scale, and Exercise Self-Efficacy Scale.ResultsTeacher care was significantly and positively associated with students’ physical education (PE) class satisfaction (B = 0.136, p < 0.001). It also had significant positive associations with exercise enjoyment (B = 0.673, p < 0.001) and exercise self-efficacy (B = 0.176, p < 0.001). Exercise enjoyment was positively associated with exercise self-efficacy (B = 0.700, p < 0.001) and PE class satisfaction (B = 0.213, p < 0.001). Exercise self-efficacy was also significantly associated with PE class satisfaction (B = 0.268, p < 0.001). Further mediation analysis indicated that exercise enjoyment and exercise self-efficacy jointly mediated the relationship between teacher care and PE class satisfaction.ConclusionThis study enriches the theoretical understanding of motivational and affective mechanisms in physical education and offers practical implications for improving teaching quality and student well-being. Limitations include the cross-sectional design and self-report data, which restrict causal inference and generalizability. Future research could employ longitudinal or mixed-method approaches across more diverse educational contexts to validate and extend these findings.